The Role of Sustainable Leadership in Achieving Professional Motivation at the Education Offices in Riyadh - Al-Zaid, Bayan Saud (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the reality of applying sustainable leadership in its four areas (human relations, participation in decision-making, delegation of authority, quality of career) in Riyadh education offices from the point of view of female educational supervisors, and to reveal the level of professional motivation they have, and the obstacles facing the application of sustainable leadership in those areas, and to reveal whether there are statistically significant differences between the averages of responses of the study sample on the application of sustainable leadership due to two variables (type of supervision, years of service in supervision), and to provide proposed mechanisms to raise the level of professional motivation of Supervisors from the point of view of experts, and the study followed the descriptive-survey approach، The survey tool and the professional motivation scale were also used to collect data, and the study community consisted of (669) supervisors, and the study sample consisted of (150) supervisors, and the results showed that the reality of applying sustainable leadership in its four fields from the point of view of educational supervisors came with a level of "approval", and the level of professional motivation of Supervisors came with a level of "strongly changes (type of supervision, years of service in supervision), and that the proposed mechanisms for raising the level of The professional motivation of the supervisors, from the point of view of experts, came at the level of "strongly approved".